Pengaruh Content Marketing terhadap Purchase Decision Dimediasi Brand Trust dan Customer Engagement - Amisha Nurfitriyani; Asep Supriadi; Hayati Nupus (BADAN PENERBIT STIEPARI PRESS, 2025)
The purpose of this study is to examine how content marketing affects customers' decisions to buy Kulo Coffee products, taking into account the mediating effects of customer engagement and brand trust. This study employed a quantitative approach using a descriptive methodology. Questionnaires and a review of the literature were used to gather data. Coffee drinkers in Tangerang Regency made up the study's population, and 140 respondents were selected through the use of purposive selection and sample withdrawal through incidental sampling. This study's analysis approach makes use of SmartPLS 4's Structural Equation Modeling (SEM) tool. The results indicate that is no significant effect of Content Marketing on Purchase Decision Brand Trust has a positive and significant impact on Purchase Decision, that Content Marketing has a positive and significant effect on Brand Trust, that Brand Trust has a positive and significant impact on Purchase Decision, that Content Marketing has a positive and significant effect on Customer Engagement, that Brand Trust can mediate the effect of Content Marketing on Purchase Decision, and that Customer Engagement can mediate the effect of Content Marketing on Purchase Decision.